Foundation Drupal 7 - Townsend, Robert J.; Pakrul, Stephanie; SpringerLink (Online service) (Berkeley, CA : Apress, 2010)
Drupal is a content management framework that powers web sites from simple online brochures to more advanced sites including social networking sites, blogs, e-commerce sites, business portals, and more. It is free, open source software that allows anyone to quickly and easily build web sites. Its full range of modules$1 (Bincluding user permissions, security mechanisms, JavaScript menus, image uploaders, WYSIWYG editors, and more$1 (Bhelps you easily create the foundation for a powerful web site. With its templating system (and a few tips and tricks), any graphic design file can be used to create a Drupal web site. Foundation Drupal 7 covers all the topics necessary to quickly build Drupal-powered web sites, explaining in simple terms how Drupal works and providing you with concepts, tips, and code snippets for every step of the development process. From setting up a Drupal-ready web host and installing Drupal to using the administrative interface and configuring a site from start to finish, there is something here for everyone. In addition to thoroughly discussing all of Drupal$1 (Bs core modules, this book reviews more than 50 contributed modules, including WYSIWYG HTML editors, JavaScript drop-down menus, web forms, and even the powerful Views module. Stephanie Pakrul, creator and maintainer of the Fusion theme, coauthors a chapter on how to lay out and add graphics to a site through Drupal$1 (Bs administrative section. After reading this book, you will walk away with everything you need to know to quickly and successfully build a Drupal-powered web site. Whether you$1 (Bre an experienced Drupal site builder looking to expand your skills, a web developer or designer interested in learning Drupal, or a weekend hobbyist looking to build your first site, Foundation Drupal 7 will give you the knowledge and inspiration you need to bring your ideas to life.s
An Overview of Drupal -- Setting Up a Web Host and Installing Drupal -- Configuring a Basic Drupal Web Site -- Adding Content Types and Fields -- People, Roles, and Permissions -- Enabling and Configuring Core Modules -- Essential Contributed Modules -- Theming a Drupal Website -- Designing for a Browser -- Going Live -- Maintaining and Updating a Drupal Site -- Translating Business Requirements to Drupal Functionality.
Keywords: Computer science; Computer Science; Computer Science, general